Numeracy deficits scrutinized: Evidences of primary developmental dyscalculia - Ribeiro, Fabiana Silva; Tonoli, Marina Cury [UNESP]; De Sá Antunes Ribeiro, Diana Pancini [UNESP]; Dos Santos, Flávia Heloísa [UNESP] (American Psychological Association (APA), 2017)
The successful acquirement of mathematical skills during the school years depends on the development of numerical cognition, which can impact future personal and professional development. The present study investigated the function of numerical cognition systems in children with numeracy deficits (ND). Twenty-eight children, aged 9–10 years and of both genders, were divided into 2 groups: ND (n = 13) and typical development (TD; n = 15). We assessed numerical cognition, working memory, short-term memory, intellectual level, executive function, mathematical anxiety, depression, stress, and school performance. Children in the ND group presented poorer arithmetic performance than the TD group, indicating a 1-year developmental delay. Performance of the ND group was severely impaired (‒1.5 SD) in all of the numerical cognition systems, including numerical production, numerical comprehension, calculation, and mental number line. The lack of comorbidities or other cognitive deficits supports the argument that children in the ND group in the present sample had numerical processing deficits that suggested primary developmental dyscalculia.
Keywords: Developmental dyscalculia; Numerical cognition; Scholastic achievement; Zareki-R